New species and records of the lichen genus Graphis (Graphidaceae, Ascomycota) from Thailand. (9th September 2015) - Unknown
Abstract: One new species and six new records of the crustose lichenized genus Graphis are reported from Thailand. Graphis koratensis Pitakpong, Kraichak & Lücking sp. nov. is characterized by lirelline ascocarps with whitish grey or grey-green pruina along the slit, transversely septate ascospores, and the presence of norstictic acid. Phylogenetic analyses with two loci (mtSSU and nuLSU) show the distinct position of this new species within the genus. Six new records for Thailand are reported, including G. cincta (Pers.) Aptroot, G. jejuensis K. H. Moon et al., G. nigrocarpa Adaw. & Makhija, G. renschiana (Müll. Arg.) Stizenb., G. seminuda Müll. Arg., and G. subserpentina Nyl.